Small oral squamous cell carcinomas with nodal lymphogenic metastasis show increased infiltration of M2 polarized macrophages - An immunohistochemical analysis - Weber, Manuel; Büttner, Maike; Hyckel, Peter; Moebius, Patrick; Distel, Luitpold; Ries, Jutta; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Journal of Cranio-Maxillofacial Surgery, 2014)
In solid malignancies the influence of immunological parameters - especially of macrophages - on invasiveness, metastatic potential and prognosis has been shown. There are no studies quantitatively analysing the macrophage polarization in oral squamous cell carcinoma (oscc). The aim of this study was to correlate macrophage polarization in the epithelial and stromal compartment of oscc with histopathologic parameters.T1 and T2 oscc samples (n = 34) were used. Automated immunohistochemical staining detected CD68, CD11c, CD163 and MRC1 positive cells. All samples were completely digitalized using whole slide imaging and the number of stained cells per area was assessed quantitatively.Primary tumours with lymphogenic metastasis (N+) showed a significantly (p < 0.05) increased count of CD68, CD11c, CD163 and MRC1 positive cells in the epithelial fraction compared to N0 tumours. The ratio of CD163 positive cells (M2 macrophages) to CD68 positive cells (M1 and M2 macrophages) was significantly (p < 0.05) increased in N+ tumours.An increased macrophage infiltration and an increased M2 polarization in primary oral squamous cell carcinomas with lymphogenic metastasis was shown. Macrophages that migrated into the epithelial tumour fraction seem to be of special biological importance. The results indicate a central role of macrophages in the progression of oscc.
EVALuna2:18151